DEVELOP AN EMPOWERMENT MODEL FOR POOR FARMERS IN JENEPONTO, SOUTH SULAWESI - Saparuddin M (Fakultas Ekonomi Universitas Negeri Jakarta, 2015)
The objective of this study is to develop an empowerment model for poor farmers in Jeneponto, South Sulawesi. This study used descriptive method, with three approaches, economics, social and cultural, and institutional approach. Results of this study are: 1) the farmers in Jeneponto have limited knowledge of modern agriculture. 2) most of poor farmers in Jeneponto was not caused by the condition of natural resources. 3) some of agriculture comoditions could enhance optimally with good water management system. 4) low rate of savings caused the low rate investation and productivity. Keyword : farmer empowerment, poverty